1994
DOI: 10.1175/1520-0426(1994)011<0964:mohati>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Humidity and Temperature in the Marine Environment during the HEXOS Main Experiment

Abstract: Accurate measurement of fluctuations in temperature and humidity are needed for determination of the surface evaporation rate and the air-sea sensible heat flux using either the eddy correlation or inertial dissipation method for flux calculations. These measurements are difficult to make over the ocean, and are subject to large errors when sensors are exposed to marine air containing spray droplets. All currently available commercial measurement devices for atmospheric humidity require frequent maintenance. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Briefly, the HEXOS data came directly from tabulations in DeCosmo's (1991) thesis. Smith et al (1992), Katsaros et al (1994), andDeCosmo et al (1996) provided thorough descriptions of the instruments and the measurements. The HEXOS set includes eddy-covariance measurements of the friction velocity (u * ) and the total sensible (H s,T ) and latent (H L,T ) heat fluxes on the Meetpost Noordwijk platform in the North Sea.…”
Section: Datamentioning
confidence: 99%
“…Briefly, the HEXOS data came directly from tabulations in DeCosmo's (1991) thesis. Smith et al (1992), Katsaros et al (1994), andDeCosmo et al (1996) provided thorough descriptions of the instruments and the measurements. The HEXOS set includes eddy-covariance measurements of the friction velocity (u * ) and the total sensible (H s,T ) and latent (H L,T ) heat fluxes on the Meetpost Noordwijk platform in the North Sea.…”
Section: Datamentioning
confidence: 99%
“…Modern 3D sonic anemometers often contain built-in algorithms to detect and exclude spurious signals produced by particles in the sound path, but these function best in light precipitation (Peters and Fischer 1998). When the sonic transducers become coated with water or are struck by large rain drops, the output usually is severely contaminated (Katsaros et al 1994). A hurricane intercept team at Texas Tech University has been deploying 3D sonic anemometers as part of their instrument package, but the output has generally been too contaminated to be of use (J. L. Schroeder 2004, personal communication).…”
Section: Development and Designmentioning
confidence: 99%
“…They found these sensors to be reliable, except in temperatures of Ϫ20°C, with no hysteresis effects occurring after saturation. Although there has been one report of hysteresis effects at high humidities and very low temperatures for the Rotronics MP-100 based on data collected during the Humidity Exchange over the Sea (HEXOS) experiment in 1986 (Katsaros et al 1994), other studies have not found any evidence of this (e.g., Breaker et al 1998a). Subsequent manufacturing improvements to the MP-100 sensor may have eliminated this problem (Breaker et al 1998b), making these sensors more reliable at high humidities.…”
Section: Datamentioning
confidence: 99%